Isolation and Molecular Characterization of Local Goat Milk Casein for Nutraceutical Value - Mohd Akmal, Azhar; Norshafiqa, Salim (2016)
Goat milk possesses a variety of biochemical composition, technological properties and bacteriological quality depending on genetic factors. Casein is the main protein that derived from goat milk which consists of alpha, beta and kappa casein. Nowadays, people are suffering from cow milk allergy. Goat milk can be used as alternative by people who suffer from cow milk allergy. The aim of this study is to extract casein from local breed goat milk and identify the molecular characterization of casein for nutraceutical value. The casein was successfully extracted using extraction method. Extraction is a common technique used to separate a desired substance when it is mixed with other components. As for the result of the extraction, the morphology of casein extracted from local goat milk was observed to be white in colour and was in semi-solid form. The average percentage of casein obtained was 24.25%. Then, the casein was analysed by running it in the SDS-Page. The major fraction is β-casein and the minor is α-casein that can be seen between 20kDa and 30kDa. The result obtained in this study indicates the presence of casein in local goat milk and has potential in future to be used as an alternative by people who suffer from cow milk allergy.